The Effect of health education package on the reproductive health knowledge, beliefs, life skills and behavior of in-school youth a comparative study of approaches - Villarta, Bethel Buena P.
BACKGROUD: As of 1995, more than one fifth (20.5%) of the Philippine population is composed of young people aged 15 to 24 years old, the adolescents and youth. Most of the health concerns among adolescents are centered on the rapid changes that are happening to them not only physically but also emotionally and psychologically as well. Of particular concern is the care of their reproductive health.{{{{OBJECTIVES OF THE STUDY: The general objective of this study is to compare the effects of the Adolescent Reproductive Packages for adolescents and adolescents with their parents on the reproductive health knowledge, beliefs, behavioral intentions, life skills and behavior of In-School Youth.{{{{SAMPLE: A convenience sample of 150 In-School youth from three municipalities of the Province of Nueva Vizcaya were selected for the study. They were distributed as follows: 50 from Quezon composed the control group, 48 from Dupax del Sur composed the Adolescents Only group and 52 from Villaverde composed the Adolescents and Parents group. In addition to the In-School Youth, 36 parents of adolescents from Villaverde also participated in the study.{{{{METHODOLOGY: The study used a quasi-experimental pre test, post test design. Baseline data were gathered through self-administered questionnaire and knowledge test, with all the study participants taking the tests in one day. Post tests were taken two weeks after the end of the trainings conducted in each of the study sites. The control group tool their test in the same week that the Adolescents Only group took theirs. Representatives of parents participated in pre and post training focus group discussions. The level of life skills after the training were observed during the "farewell parties" which served as venues for simulating situations that would test the In-School Youths' life skills. Additional data were gathered through documentation of training proceedings.{{{{DATA ANALYSIS: The comparability of the groups was determined using One-way ANOVA. Analysis of the differences between pre and post test scores used the Paired t-test if the difference in score is 5 and above ...